MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

A universal chemical strategy towards the use of diluent for carbonate localized high-concentration electrolytes - Qingjiang Liu; Min Niu; Xingyu Chen; Zongfan Yang; Yan Meng; Yi-Bing Wang; Xian-Xin Feng; Liwei Dong; Lin Mei; Libao Chen; Changsong Dai; Bo Song; et al. (Chemical Engineering Journal, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

Isotopic compositions reveal distinct roles of in-cloud and below-cloud scavenging in dissolved and particulate mercury in precipitation - Zixuan Wang; Tao Li; Hongming Cai; Mei Meng; Jiubin Chen; Lin Du; Jiebo Zhen; Ping Du; Yan Wang (Atmospheric Environment, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

Corrigendum to “OsCOPT7 is involved in copper accumulation and transport through xylem” [J Hazard Mater 477 (2024) 135245] - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2026)

Multi-pathway and gut microbiota mechanisms underlying the antioxidant effects of formononetin - Mei Xie; Lingrui Kong; Yan Chen; Lin Hou; Jian Hou (South African Journal of Botany, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

L-arginine enhances skeletal muscle energy metabolism and maintains mitochondrial homeostasis to promote locomotor function in zebrafish embryos - Qiu-Yan Chen; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Bioaccumulation of trace elements and ecological risks induced by petroleum extraction in Shengli oilfield, China - Hong Yang; Xuexin Gong; Yixin Tan; Siyang Zhang; Mei He; Bo Shao; Lei Tian; Yan Lin (Environmental Geochemistry and Health, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Intercropping reduces soil erosion, improves soil conditions, and increases productivity of a Camellia oleifera plantation - Zeyao Zhao; Lin Chen; Wanwan He; Wenjun Xie; Byron B. Lamont; Longsheng Chen; Li Mei; Zhaogui Yan (Plant and Soil, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Experimental Analysis of Structure Rockburst in Rock-Like Materials Under Gradient Loading Using Coupled Infrared Thermography and Acoustic Emission - Yuanhang Zhang; Yuanyou Xia; Manqing Lin; Zhichao Wang; Jian Huang; Yaofeng Yan; Wanquan Mei (Rock Mechanics and Rock Engineering, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Eight previously undescribed flavonoids and four previously undescribed bibenzyls from Macaranga kurzii and their potential antiviral activities - Yan-Zi Ma; Ding-Cheng Zhang; Liu Yang; Xue-Wen Wu; Bo Li; Muhammad Aurang Zeb; Yuan-Lin Kong; Xue-Mei Zhou; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

A machine learning and box modeling approach to comparing the atmospheric chemistry of high- and low-ozone and PM₂.₅ episodes - Ahsan Mozaffar; Yan-Lin Zhang; Yihang Hong; Mei-Yi Fan; Yu-Chi Lin (Atmospheric Research, 2026)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

The effect and mechanism of sublethal injury by lactic acid on Salmonella Typhimurium planktonic and biofilm cells - Mengjiao Zhang; Yunshuang Man; Rongrong Yang; Yudi Wang; Dongling Yan; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Microbiology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Restoring Retinoic Acid: Alleviating Autism-Like Behaviors in Sox5-Deficient Mice - Lanyan Lin; Yongxing Lai; Ainong Mei; Yan Chen; Fan Lin (Neuroscience Bulletin, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Recyclable, photothermal dual responsive shape memory epoxy vitrimers containing dynamic oxime-carbamate bonds, dynamic ester bonds and hydrogen bonds based on vegetable oil - Xiaoqi Xie; Shouhai Li; Mei Li; Haiyang Ding; Mingtao Lin; Lina Xu; Na Yao; Qingyuan Feng; Xiaohua Yang; Xiao Feng; Yan Zhang; Yi Xing (Chemical Engineering Journal, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Glycation of β-Lactoglobulin with different lengths sugar chains: Impacts on structure, allergenicity and flavor profile - Wen-mei Chen; Lin Zou; Yan-hong Shao; Zong-cai Tu; Jun Liu (Food Chemistry, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Passivation mechanism driven selective leaching for recycling spent LiFePO4 lithium-ion batteries - Yurong Han; Menglong Yan; Yinzhuang Fang; Yifeng Han; Yi Chen; Liangyou Lin; Jingwen Qian; Tao Mei; Xianbao Wang (Journal of Environmental Chemical Engineering, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

Parallel floral evolution of Lilium species pollinated by pierid butterflies - Yun-Bo Duan; Hong-Qiang Lin; Zhe Chen; Chang-Qiu Liu; Yu-Mei Yuan; Yun-Dong Gao; Mei-Yan Lei; Mao-Lin Wang (Flora, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Boosted catalytic soot oxidation by hierarchical hollow cobalt oxide constructed from a Template-Sacrificial Method: Promoting Roles of morphologies and oxygen vacancies - Yu-Chih Tsai; Mei-Chen Wan; Shen Yan Lin; Vo Thi Thanh Thuy; Nguyen Nhat Huy; Duong Dinh Tuan; Jechan Lee; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Performances and mechanisms of catalytic ozonation for paint wastewater via catalysts of Fe-Mn deposited within graphitized beads of γ-Al2O3 - Mei Dai; Chunping Yang; Liusiyu Yang; Yan Lin; Shanying He; Xiang Li; Qiuya Niu; Shaohua Wu (Journal of Cleaner Production, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Short-term coalbed methane concentration prediction and early warning based on the STL-ENN-GRU hybrid model - Kangle Li; Lin Jiang; Yan Zhang; Mei Wang; Yuancheng Li; Kun Yang (Earth Science Informatics, 2025)

Platelet-hitchhiking biomimetic nanoplatforms pry precisely tumor seed and growing soil for inhibiting tumor recurrence and metastasis - Yan Zhang; Weiting Sun; Guozheng Xing; Dunwan Zhu; Lin Mei; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Hydroxyl radicals in ozone-based advanced oxidation of organic contaminants: A review - Mei Dai; Qiuya Niu; Shaohua Wu; Yan Lin; Jayanta Kumar Biswas; Chunping Yang (Environmental Chemistry Letters, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Fluorescent carbon dots based on food wastes: Applications in food safety detection - Chenghao Liu; Yanqiu Mei; Qiaowen Lei; Xiaoming Ma; Xinru Nan; Yunxiao Zhu; Jing Liao; Youhong Xu; Yan Luo; Hanqiang Zhang; Min Yang; Xiaofeng Lin; et al. (Chemical Engineering Journal, 2024)

Exploring the therapeutic potential of Cassia species on metabolic syndrome: A comprehensive review - Lin Xu; Yue Yang; Bin Li; Hong Dong Liu; Ling Xia Xu; Dong Mei Yan; Xue Mei Gao (South African Journal of Botany, 2024)

Important contributions of natural gas combustion to atmospheric nitrate aerosols in China: Insights from stable nitrogen isotopes - Yu-Chi Lin; Mei-Yi Fan; Yihang Hong; Mingyuan Yu; Fang Cao; Yan-Lin Zhang (Science Bulletin, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Conjugated microporous polymer derived hierarchically porous N-rich nanocarbon as a durable electrocatalyst for oxygen reduction reaction in Zn-air battery - Lunjie Liu; Zian Xu; Yu Xia; Mei-Yan Gao; Qin Jin; Baobing Zheng; Chongxuan Liu; Shaoqing Chen; Zhe Zhang; Hsing-Lin Wang (Chemical Engineering Journal, 2024)

OsCOPT7 is involved in copper accumulation and transport through xylem - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

An optically responsive cancer vaccine for inducing robust anti-tumor immunity by apoptotic body carrying nanoadjuvants - Limin Jin; Shupei Sheng; Yan Zhang; Weiting Sun; Lin Mei; Dunwan Zhu; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

pH-responsive coacervate with adrenergic nerve blockade function inhibits triple-negative breast cancer metastasis by blocking nerve-tumor-immune loop - Jieting Chen; Chaoming Mei; Yan Tan; Fan Yang; Shirui Yang; Xin Wen; Xin Peng; Yong Lin; Dan Li (Chemical Engineering Journal, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Node Load and Location-Based Clustering Protocol for Underwater Acoustic Sensor Networks - Haodi Mei; Haiyan Wang; Xiaohong Shen; Zhe Jiang; Yongsheng Yan; Lin Sun; Weiliang Xie (Journal of Marine Science and Engineering, 2024)
Clustering protocols for underwater acoustic sensor networks (UASNs) have gained widespread attention due to their importance in reducing network complexity. Congestion occurs when the intra-cluster load is greater than the upper limit of the intra-cluster information transmission capacity, which leads to a dramatic deterioration of network performance despite the reduction of network complexity. To avoid congestion, we propose a node load and location-based clustering protocol for UASNs (LLCP). First, a node load and location-based optimization mechanism is proposed. The number of cluster members is optimized based on node load and location to maximize the number of cluster members while avoiding congestion. Then, a node degree and location-based cluster member selection mechanism is proposed to select the optimal cluster members. Finally, a priority-based clustering mechanism is proposed. The node clustering order is adjusted based on the clustering priority to maximize the reduction of network complexity by increasing the average number of cluster members. Simulation results show that our proposed LLCP minimizes the network complexity while avoiding congestion.

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Improved piezo-photocatalysis for aquatic multi-pollutant removal via BiOBr/BaTiO3 heterojunction construction - Shiqi Zhong; Yabin Wang; Yan Chen; Xingan Jiang; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiao Wu (Chemical Engineering Journal, 2024)

Arsenic effectively improves the degradation of fluorene by Rhodococcus sp. 2021 under the combined pollution of arsenic and fluorene - Hong-Peng Shi; Ying-Hao Zhao; Mei-Lin Zheng; Cheng-Yan Gong; Lei Yan; Ying Liu; Yong-Ming Luo; Zhi-Pei Liu (Chemosphere, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Viral community distribution, assembly mechanism, and associated hosts in an industrial park wastewater treatment plant - Wenqing Hong; Hong Mei; Xianyang Shi; Xiaoxing Lin; Shuijing Wang; Renjie Ni; Yan Wang; Liyan Song (Environmental Research, 2024)

Chemical structure of hydrocarbons significantly affects removal performance and microbial responses in gas biotrickling filters - Xin Wu; Yan Lin; Yongyi Wang; Mei Dai; Shaohua Wu; Xiang Li; Chunping Yang (Bioresource Technology, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Human health risk assessment of volatile organic compounds in oil-based drill cuttings of shale gas - Chao-qiang Wang; Yan Ying; Xu-dong Mei; Zhong Chen; Feng-lin Xu (Environmental Science and Pollution Research, 2024)

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Bioaccumulation, biomagnification, and ecological risk of trace metals in the ecosystem around oilfield production area: A case study in Shengli Oilfield - Qian Ning; Bo Shao; Xin Huang; Mei He; Lei Tian; Yan Lin (Environmental Monitoring and Assessment, 2024)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

The Daily Intake Levels of Copper, Selenium, and Zinc Are Associated with Osteoarthritis but Not with Rheumatoid Arthritis in a Cross-sectional Study - Wei-ming Yang; Jiao-feng Lv; Yuan-yuan Wang; Yan-mei Xu; Jin Lin; Jing Liu; Juan-juan Chen; Xiao-zhong Wang (Biological Trace Element Research, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

The growth inhibitory effects and non-targeted metabolomic profiling of Microcystis aeruginosa treated by Scenedesmus sp - Xiao-lin Zhang; Qian-qian Zhu; Chuan-yue Chen; Bing Xie; Bin-guo Tang; Mei-hua Fan; Qun-ju Hu; Zhi Liao; Xiao-jun Yan (Chemosphere, 2023)

Proteomic analysis of Staphylococcus aureus exposed to bacteriocin XJS01 and its bio-preservative effect on raw pork loins - Jian-Ping Ying; Gang Wu; Yan-Mei Zhang; Qi-Lin Zhang (Meat Science, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

Identification and functional analysis of endoplasmic reticulum oxidoreductase 1 (ERO1) from the green mud crab Scylla paramamosain: The first evidence of ERO1 involved in invertebrate immune response - Chen-Yang Lin; Yan-Mei Zhang; Wen-Bin Xu; Miao-An Shu; Wei-Ren Dong (Fish & Shellfish Immunology, 2023)

Correction: Effects of Pharmacological Intervention on Recovery After Sevoflurane Anesthesia in Children: A Network Meta-analysis of Randomized Controlled Trials - Cong-mei Wang; Yan Zhang; Wei-can Chen; Shu Lin; He-fan He (Molecular Neurobiology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Effects of Pharmacological Intervention on Recovery After Sevoflurane Anesthesia in Children: a Network Meta-analysis of Randomized Controlled Trials - Cong-mei Wang; Yan Zhang; Wei-can Chen; Shu Lin; He-fan He (Molecular Neurobiology, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Palladium-catalyzed Sonogashira coupling to synthesis of gem‑difluoroenynes - Lin Li; Yan Mei; Junlei Zhang; Kehan He; Fei Pan (Journal of Fluorine Chemistry, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China - Yu-Chi Lin; Zi-Jin Zhang; Meng-Yao Cao; Mei-Yi Fan; Ahsan Mozaffar; Ming-Yuan Yu; Feng Xie; Yan-Lin Zhang (Atmospheric Environment, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

Seasonal variations of low molecular alkyl amines in PM2.5 in a North China Plain industrial city: Importance of secondary formation and combustion emissions - Xiao-Ying Yang; Fang Cao; Mei-Yi Fan; Yu-Chi Lin; Feng Xie; Yan-Lin Zhang (Science of The Total Environment, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Temporal specificity of IL-6 knockout in enhancing the thermogenic capability of brown adipose tissue - Mei Dong; Cheng Gao; Yanxin Jia; Weijia Xu; Yan Liu; Xin Wen; Qingxin Liu; Hai Lin; Haifang Li (Journal of Physiology and Biochemistry, 2022)

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

The management of bone defect using long non-coding RNA as a potential biomarker for regulating the osteogenic differentiation process - Jia-lin Liu; Yan-shi Liu; Mei-jie Zheng; Hui-yu He (Molecular Biology Reports, 2022)
Tissue engineered bone brings hope to the treatment of bone defects, and the osteogenic differentiation of stem cells is the key link. Inducing osteogenic differentiation of stem cells may be a potential approach to promote bone regeneration. In recent years, lncRNA has been studied in the field increasingly, which is believed can regulate cell cycle, proliferation, metastasis, differentiation and immunity, participating in a variety of physiology and pathology processes. At present, it has been confirmed that certain lncRNAs regulate the osteogenesis of stem cells and take part in mediating signaling pathways including Wnt/β-catenin, MAPK, TGF-β/BMP, and Notch pathways. Here, we provided an overview of lncRNA, reviewed its researches in the osteogenic differentiation of stem cells, emphasized the importance of lncRNA in bone regeneration, and focused on the roles of lncRNA in signaling pathways, in order to make adequate preparations for applying lncRNA to bone tissue Engineering, letting it regulate the osteogenic differentiation of stem cells for bone regeneration.

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

Depression Augments Plasma APOA4 without Changes of Plasma Lipids and Glucose in Female Adolescents Carrying G Allele of APOA4 rs5104 - Qi Wei Guo; Yan Jun Si; Yi Lin Shen; Xu Chen; Mei Yang; Ding Zhi Fang; Jia Lin (Journal of Molecular Neuroscience, 2021)

Enhanced treatment of shale gas fracturing waste fluid through plant-microbial synergism - Bo Shao; Xu Tan; Ju-Long Li; Mei He; Lei Tian; Wen-Jie Chen; Yan Lin (Environmental Science and Pollution Research, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Low ambient temperature increases hospital re-admissions for systemic lupus erythematosus in humid subtropical region: a time series study - Qian Wu; Zhiwei Xu; Yi-Lin Dan; Peng Wang; Yan-Mei Mao; Chan-Na Zhao; Yan-Feng Zou; Dong-Qing Ye; Wenbiao Hu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

The chemical constituents from the active fractions of Eleutherine bulbosa with their antimicrobial activity - Hai Jiang; Wen-Jing Man; A-Jiao Hou; Lin Yang; Xu-Dong Xing; Mei-Ling Yan; Xin-Yue Guo; Liu Yang (Natural Product Research, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Endothelial Notch activation promotes neutrophil transmigration via downregulating endomucin to aggravate hepatic ischemia/reperfusion injury - Peiran Zhang; Kangyi Yue; Xinli Liu; Xianchun Yan; Ziyan Yang; Juanli Duan; Congcong Xia; Xinyuan Xu; Mei Zhang; Liang Liang; Lin Wang; Hua Han (Science China Life Sciences, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Age- and Nicotine-Associated Gene Expression Changes in the Hippocampus of APP/PS1 Mice - Jie Yang; Yan Long; De-Mei Xu; Bing-Lin Zhu; Xiao-Juan Deng; Zhen Yan; Fei Sun; Guo-Jun Chen (Journal of Molecular Neuroscience, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Lignans, flavonoids and coumarins from Viola philippica and their α-glucosidase and HCV protease inhibitory activities - Ya-Li Wang; Lin Zhang; Meng-Yan Li; Li-Wei Wang; Chao-Mei Ma (Natural Product Research, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Mercury–Organic Matter Interactions in Soils and Sediments: Angel or Devil? - Mei He; Lei Tian; Hans Fredrik Veiteberg Braaten; Qingru Wu; Jie Luo; Li-Mei Cai; Jiang-Hui Meng; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2019)

Posttraumatic Stress Disorder Augments Plasma Triglycerides in TT Homozygotes of rs495225 at Growth Hormone Secretagogue Receptor Gene - Mi Su; Yan Jun Si; Qi Wei Guo; Mei Yang; Xu Chen; Jia Lin; Ding Zhi Fang (Biochemical Genetics, 2019)

Large-scale analysis of small RNAs derived from traditional Chinese herbs in human tissues - Fengming Huang; Jianchao Du; Zhu Liang; Zhichao Xu; Jiantao Xu; Yan Zhao; Yexuan Lin; Song Mei; Quan He; Jindong Zhu; Qiang Liu; Yanxu Zhang; et al. (Science China Life Sciences, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Cyproheptadine Regulates Pyramidal Neuron Excitability in Mouse Medial Prefrontal Cortex - Yan-Lin He; Kai Wang; Qian-Ru Zhao; Yan-Ai Mei (Neuroscience Bulletin, 2018)

A new antiviral pregnane from a gorgonian-derived Cladosporium sp. fungus - Mei-Lin Yu; Fei-Fei Guan; Fei Cao; Yan-Lai Jia; Chang-Yun Wang (Natural Product Research, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Lipoprotein (a) as a Predictor of Early Stroke Recurrence in Acute Ischemic Stroke - Xiao-Wu Hong; Dong-Mei Wu; Jun Lu; Yuan-Lin Zheng; Wen-Jun Tu; Jing Yan (Molecular Neurobiology, 2018)

PAX3 Promotes Cell Migration and CXCR4 Gene Expression in Neural Crest Cells - Man Xu; Yongle Li; Jinfeng Du; Hengrong Lin; Sixian Cao; Zuming Mao; Ronghua Wu; Mei Liu; Yan Liu; Qiyou Yin (Journal of Molecular Neuroscience, 2018)

Environmental security control of resource utilization of shale gas’ drilling cuttings containing heavy metals - Chao-qiang Wang; Xiao-yan Lin; Chun Zhang; Xu-dong Mei (Environmental Science and Pollution Research, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Iron supply prevents Cd uptake in Arabidopsis by inhibiting IRT1 expression and favoring competition between Fe and Cd uptake - Xiao Lin He; Shi Kan Fan; Jun Zhu; Mei Yan Guan; Xing Xing Liu; Yong Song Zhang; Chong Wei Jin (Plant and Soil, 2017)

A study on the oil-based drilling cutting pyrolysis residue resource utilization by the exploration and development of shale gas - Chao-qiang Wang; Ji-zhong Jin; Xiao-yan Lin; De-ming Xiong; Xu-dong Mei (Environmental Science and Pollution Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Dietary flavones counteract phorbol 12-myristate 13-acetate-induced SREBP-2 processing in hepatic cells - Yan Qin Tan; Tsz Yan Wong; Shu-mei Lin; Lai K. Leung (Molecular and Cellular Biochemistry, 2017)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Dichromatism in the commensal shrimp Anchistus miersi (De Man, 1888) - Mei Lin Neo; Bee Yan Lee; Kareen Vicentuan; Peter Alan Todd (Marine Biodiversity, 2015)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Microcalorimetry studies of the antimicrobial actions of Aconitum alkaloids - Yan-bin Shi; Lian Liu; Wei Shao; Ting Wei; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

Up-regulation of nicotinamide phosphoribosyltransferase and increase of NAD+ levels by glucose restriction extend replicative lifespan of human fibroblast Hs68 cells - Nae-Cherng Yang; Tuzz-Ying Song; Yan-Zin Chang; Mei-Yau Chen; Miao-Lin Hu (Biogerontology, 2015)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

A two-step local smoothing approach for exploring spatio-temporal patterns with application to the analysis of precipitation in the mainland of China during 1986–2005 - Na Yan; Chang-Lin Mei (Environmental and Ecological Statistics, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Novel triterpenoid saponins from the seeds of Celosia argentea L. - Qing Bin Wu; Yan Wang; Lin Liang; Qian Jiang; Mei Li Guo; Jun Jie Zhang (Natural Product Research, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Photooxidation of arsenite by natural goethite in suspended solution - Yajie Wang; Jing Xu; Yan Zhao; Lin Zhang; Mei Xiao; Feng Wu (Environmental Science and Pollution Research, 2013)

Winter wheat mapping using temporal signatures of MODIS vegetation index data - Huasheng Sun; Aigong Xu; Hui Lin; Lianpeng Zhang; Yan Mei (International Journal of Remote Sensing, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Ginsenoside Rg1 inhibits autophagy in H9c2 cardiomyocytes exposed to hypoxia/reoxygenation - Zi-Long Zhang; Yan Fan; Mei-Lin Liu (Molecular and Cellular Biochemistry, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Isolation, characterization and colonization of 1-aminocyclopropane-1-carboxylate deaminase-producing bacteria XG32 and DP24 - Mei-Xia Wang; Jia Liu; Shuang-lin Chen; Shu-Zhen Yan (World Journal of Microbiology and Biotechnology, 2012)

Quantification of ecosystem carbon exchange characteristics in a dominant subtropical evergreen forest ecosystem - Yue-Lin Li; Guo-Yi Zhou; De-Qiang Zhang; Katherine Owen Wenigmann; Dennis Otieno; John Tenhunen; Qian-Mei Zhang; Jun-Hua Yan (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Association between SNP rs1800875, serum chymase and immunoglobulin E levels in patients with coronary heart disease - Chun-na Jin; Hong Ma; Yan Lin; Jian-an Wang; Mei-xiang Xiang (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of perinatal thyroid hormone deficiency on expression of rat hippocampal conventional protein kinase C isozymes - Hong-Mei Zhang; Ning Lin; Yan Dong; Qing Su; Min Luo (Molecular and Cellular Biochemistry, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

H2S Protects Hippocampal Neurons from Anoxia–Reoxygenation Through cAMP-Mediated PI3K/Akt/p70S6K Cell-Survival Signaling Pathways - Jian-Lin Shao; Xiao-Hong Wan; Yan Chen; Chun Bi; Hong-Mei Chen; Ying Zhong; Xin-Hua Heng; Jin-Qiao Qian (Journal of Molecular Neuroscience, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

MaSERK1 Gene Expression Associated with Somatic Embryogenic Competence and Disease Resistance Response in Banana (Musa spp.) - Xia Huang; Xiao-Yan Lu; Jie-Tang Zhao; Jie-Kai Chen; Xue-Mei Dai; Wang Xiao; Ya-Ping Chen; Yun-Feng Chen; Xue-Lin Huang (Plant Molecular Biology Reporter, 2010)

Effect of PARP-1 deficiency on DNA damage and repair in human bronchial epithelial cells exposed to Benzo(a)pyrene - Gong-hua Tao; Lin-qing Yang; Chun-mei Gong; Hai-yan Huang; Jian-dong Liu; Jian-jun Liu; Jian-hui Yuan; Wen Chen; Zhi-xiong Zhuang (Molecular Biology Reports, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Effects of cannabinoid CB1 receptor antagonist rimonabant in consolidation and reconsolidation of methamphetamine reward memory in mice - Lu-lu Yu; Xue-yi Wang; Mei Zhao; Yu Liu; Yan-qin Li; Fang-qiong Li; Xiaoyi Wang; Yan-xue Xue; Lin Lu (Psychopharmacology, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

New norsesquiterpene and sesquiterpene from a soft coral of the genus Nephthea - Ruo-Lin Yang; Yun-Yan Kuang; Jing-Yu Su; Long-Mei Zeng (Natural Product Research, 2008)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)